Successful deep well stimulation utilizing high proppant concentrations - 337543 Holditch, Stephen A.; Ely, John; Society of Petroleum Engineers of AIME (Dallas, Tex. : American Institute of Mining, Metallurgical and Petroleum Engineers, 1973)
51